Adolescent predictors of objectively measured physical activity and sedentary behaviour at age 42: the Amsterdam Growth and Health Longitudinal Study (AGAHLS) - Koppes Lando LJ; Twisk Jos WR; Singh Amika S; Uijtdewilligen Léonie; van Mechelen Willem; Chinapaw Mai JM (BMC, 2011)
Abstract Background This study investigated the associations of physical characteristics and personality in adolescence with physical activity and sedentary behaviour in adulthood. Findings Physical characteristics (i.e. objectively measured BMI, sum of skin folds, MOPER test battery performance), and personality (i.e. self-reported inadequacy, social inadequacy, rigidity, self-sufficiency/recalcitrance, dominance, achievement motivation, facilitating anxiety, debilitating anxiety, and social desirability) were assessed in 217 adolescent boys (Mean 13.0, SD 0.6) and girls (Mean 12.9, SD 0.6). Twenty-nine years later, at the age of 42, their physical activity and sedentary behaviour were assessed by means of accelerometry. Boys who scored lower on self-sufficiency/recalcitrance and higher on facilitating anxiety spent more time sedentary in adulthood. Girls with a superior standing high jump performance, and a lower score on social desirability spent more time sedentary in adulthood. In contrast with sedentary behaviour, physical activity at age 42 year could not be predicted by physical characteristics or personality in adolescence. Conclusions Sedentary behaviour in adulthood was partly explained by physical characteristics and/or personality in adolescence. Thus, our results suggest that it may be possible to identify people who are at risk of becoming sedentary at a rather young age.